Diamine monomer cross-linked modified fluorine-containing ferroelectric polymer, preparation method and device

Through the technical means of cross-linking of diamine monomers to modify fluorine-containing ferroelectric polymers, the problem of the reduction of leakage current and breakdown field strength of polyvinylidene fluoride and its copolymer derivatives under high electric fields is solved, and efficient dielectric energy storage performance and charge and discharge efficiency are achieved.

CN119570179AActive Publication Date: 2025-03-07SHENZHEN UNIV

Patent Information

Application Number
CN202411758583.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing polyvinylidene fluoride and its copolymer derivatives are prone to leakage current under high electric fields, resulting in increased conductivity loss, reduced charge and discharge efficiency, and significantly reduced breakdown field strength, affecting the stability of power equipment.

Method used

The modified fluoroferoelectric polymer is used to cross-link diamine monomers, and a high-temperature cross-linking reaction is carried out by cross-linking semi-crystalline thermoplastic fluoroferoelectric polymer with diamine cross-linking agent to form a thin film with a light cross-linking network to improve dielectric energy storage performance.

Benefits of technology

Under a strong electric field above 400MV/m, the prepared film exhibits high breakdown field strength, dielectric constant and discharge energy density, significantly improves the charge and discharge efficiency, and is simple in process and low in raw material costs, making it suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570179A_ABST
    Figure CN119570179A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric materials, in particular to a diamine monomer crosslinking modified fluorine-containing ferroelectric polymer, a preparation method and a device. The diamine monomer cross-linked modified fluorine-containing ferroelectric polymer comprises the following components: a semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and a diamine cross-linking agent, the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer is polyvinylidene fluoride with ferroelectricity and a copolymer derivative thereof; the diamine cross-linking agent is short-chain diamine containing a rigid structure; the mass fraction of the diamine cross-linking agent is 0.25%-10% compared with the total mass fraction. The thin film prepared by the invention meets the application requirements of improvement of dielectric constant, reduction of dielectric loss, reduction of leakage current, improvement of breakdown field strength and the like in a high electric field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric materials, and in particular to a diamine monomer cross-linked modified fluorine-containing ferroelectric polymer, a preparation method and a device. Background Art

[0002] Film capacitors based on polymer dielectrics play an irreplaceable role in the field of electronics and electrical due to their fast charging and discharging speed, high power density, good voltage resistance, self-healing properties, and chemical corrosion resistance. With the increasing demand for miniaturization and lightweight applications of electronic equipment, higher requirements are placed on the energy storage density of polymer dielectrics. Compared with increasing the dielectric constant, increasing the working voltage of the capacitor has a more obvious effect on improving energy density. However, under high electric fields, carriers are more likely to obtain enough energy to cause leakage current, which will be converted into Joule heat and produce large conductivity losses, which will not only lead to a significant decrease in charging and discharging efficiency, but also a significant decrease in breakdown field strength, which will lead to failure and damage of power equipment. Therefore, in order to improve the energy storage density, polymer dielectrics need to have excellent dielectric properties such as high dielectric constant and low dielectric loss, as well as low conductivity loss and high breakdown field strength, so as to ensure good charging and discharging efficiency and high discharge energy density.

[0003] At present, polyvinylidene fluoride (PVDF) and its copolymer derivatives, such as poly(vinylidene fluoride-co-hexafluoropropylene) (P(VDF-HFP)), poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P(VDF-TrFE-CFE)), and other fluorine-containing ferroelectric polymers, have relatively high dielectric constants and have become the preferred materials for flexible electronics and sensors. It has five crystalline phases - α, β, γ, δ and ε. The β phase has a fully anti-planar zigzag conformation, with hydrogen atoms and fluorine atoms in opposite directions. It has the highest dipole moment and exhibits spontaneous polarization, ferroelectricity and piezoelectricity. The current mainstream method is to dope nanofillers in fluoropolymers to further regulate their crystal structure and ferroelectric properties. However, the efficacy of PVDF composites is significantly affected by the ratio of fillers to the existing β phase, and due to the poor compatibility of fillers with PVDF and poor dispersion of fillers, agglomeration will occur, resulting in a significant reduction in the breakdown field strength. Therefore, it is of great application value to study the modification methods of new fluorine-containing ferroelectric polymers with excellent dielectric energy storage properties. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a diamine monomer cross-linked modified fluorine-containing ferroelectric polymer, a preparation method and a device.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0006] In the first aspect, a diamine monomer cross-linked modified fluorine-containing ferroelectric polymer is provided, wherein the components include a semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and a diamine cross-linking agent; the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer is polyvinylidene fluoride and its copolymer derivatives having ferroelectricity; the diamine cross-linking agent is a short-chain diamine containing a rigid structure; and the mass fraction of the diamine cross-linking agent compared to the total is 0.25%-10%.

[0007] Furthermore, the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer imparts film-forming properties to the uncrosslinked film (B-stage Film), toughness to the polymer film after slight crosslinking, and basic dielectric properties and energy storage properties. The semi-crystalline thermoplastic fluorine-containing ferroelectric polymer is characterized by ferroelectric polyvinylidene fluoride and its copolymer derivatives, including but not limited to polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P(VDF-TrFE-CFE)). The molecular structures of some thermoplastic fluorine-containing ferroelectric polymers are as follows:

[0008]

[0009]

[0010] Furthermore, the diamine crosslinking agent is used to lightly crosslink the main molecular chain of PVDF and its derivative copolymers. The diamine monomer is characterized by a short-chain diamine containing a rigid structure such as a benzene ring. It includes but is not limited to at least one of diaminodiphenylmethane (DDM), diaminodiphenyl sulfone (DDS), 4,4'-diaminodiphenyl ether (ODA), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), 2,2-bis[4-(3-aminophenoxy)phenyl]sulfone (MBAPS), 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) and 9,9-bis(3-fluoro-4-aminophenyl)fluorene (FFDA), 2,2'-bis(trifluoromethyl)diaminobiphenyl (BTMB). The molecular structure of some diamine crosslinking agents is as follows:

[0011]

[0012]

[0013] Furthermore, the mass fraction of the diamine cross-linking agent is 0.5%-5% compared to the total mass fraction.

[0014] In a second aspect, a method for preparing a fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer is provided, which comprises the following steps:

[0015] A semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and a diamine monomer are subjected to a heat-induced high-temperature cross-linking reaction to prepare a lightly cross-linked fluorine-containing ferroelectric polymer film; first, the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and the diamine monomer are blended and prepared into an uncross-linked film by a solution casting method; then, the film is subjected to a high-temperature treatment in a vacuum environment to induce a cross-linking reaction between the diamine monomer and the fluorine-containing ferroelectric polymer to form a fluorine-containing ferroelectric polymer film with a lightly cross-linked network.

[0016] Furthermore, the method specifically includes the following sub-steps:

[0017] S1. The semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and the diamine crosslinking agent are dissolved in an organic solvent, heated to dissolve, and a slurry of the composition is obtained, wherein the solid content of the slurry is 0.1wt%-20wt%;

[0018] S2. The slurry is formed into a film by a solution casting method; specifically, the slurry is evenly coated on a glass substrate and baked at 60-90°C to evaporate the solvent as much as possible to obtain an uncrosslinked film;

[0019] S3. After the solvent is evaporated, the glass substrate is subjected to a cross-linking reaction at multiple temperatures between 100°C and 250°C to obtain a cross-linked film;

[0020] S4. Put the glass substrate with the cross-linked film into deionized water to peel off the film, and dry the peeled film at high temperature to obtain a diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0021] Furthermore, in step S1, the solid content of the slurry is 1wt%-2wt%.

[0022] Furthermore, in step S3, the cross-linking process is 120°C×10h+240°C×1h.

[0023] In a third aspect, a device is provided, which includes a fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer, and is used as a thin film capacitor.

[0024] The beneficial effects of the present invention are:

[0025] The prepared diamine monomer cross-linked modified fluorine-containing ferroelectric polymer has the following characteristics: excellent dielectric energy storage performance, showing excellent energy storage performance under a strong electric field above 400MV / m, for example, high breakdown field strength (E b ≥500MV / m), high dielectric constant (k≥9) and high discharge energy density (U e ≥11.6J / cm 3 ); and the preparation method is simple, the raw material cost is low, and it is relatively easy to achieve mass production, which has important industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The energy storage density and charge-discharge efficiency of the thin films obtained in Example 1 of the present invention and Comparative Examples 1, 2, and 3 vary with the electric field;

[0027] Figure 2 The energy storage density and charge-discharge efficiency of the thin films obtained in Example 2 of the present invention and Comparative Examples 1 and 4 vary with the electric field;

[0028] Figure 3 The energy storage density and charge-discharge efficiency of the thin films obtained in Example 3 of the present invention and Comparative Examples 1 and 5 vary with the electric field;

[0029] Figure 4 The energy storage density and charge-discharge efficiency of the thin films obtained in Example 4 of the present invention and Comparative Examples 1 and 6 vary with the electric field;

[0030] Figure 5 The energy storage density and charge-discharge efficiency of the thin films obtained in Comparative Examples 7, 8 and 9 of the present invention vary with the electric field;

[0031] Figure 6 The dielectric constant and dielectric loss of the thin films obtained in Examples 1, 2, 3, 4 of the present invention and Comparative Example 1 vary with frequency;

[0032] Figure 7 This is a SEM image of the film obtained in Example 1 of the present invention;

[0033] Figure 8 This is a SEM image of the film obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0035] Example 1: The raw materials involved in this example include P (VDF-HFP) and ODA.

[0036] The preparation steps are as follows:

[0037] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 4,4′-diaminodiphenyl ether (ODA) in a mass ratio of 99:1 to prepare a solution with a concentration of 1wt%. Weigh 0.198g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), 0.002g of 4,4′-diaminodiphenyl ether (ODA), and add 10ml of N,N-dimethylformamide (DMF) to prepare a solution.

[0038] 2. The above solution was dissolved under magnetic stirring at 60° C. for 10 hours to allow the solute to be fully dissolved in the solvent to obtain a P(VDF-HFP) / ODA mixed solution.

[0039] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0040] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and after naturally cooling to room temperature, a slightly cross-linked film is obtained.

[0041] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0042] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / ODA (1 wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0043] Implementation effect: The P(VDF-HFP) / ODA (1wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this embodiment has a higher dielectric constant, such as Figure 6 As shown, its dielectric constant is 8.53 at 1kHz; its energy storage density and charge and discharge efficiency are shown in Figure 1 As shown in Figure 2, the breakdown electric field strength is increased to 550MV / m and the discharge energy density is 11.56J / cm 3 The charge and discharge efficiency is 44.5%. The SEM photo of the brittle fracture of the fluorine-containing ferroelectric polymer film is shown in Figure 7 shown.

[0044] Example 2: The raw materials involved in this example include P (VDF-HFP) and HFBAPP.

[0045] The preparation steps are as follows:

[0046] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. Weigh 0.19g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 0.01g of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP), and add 10ml of DMF to prepare a solution.

[0047] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0048] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0049] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0050] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0051] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / HFBAPP (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0052] Implementation effect: The P(VDF-HFP) / HFBAPP (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this embodiment has a higher dielectric constant, such as Figure 6 As shown, its dielectric constant is 7.86 at 1kHz; its energy storage density and charge and discharge efficiency are shown in Figure 2 As shown in Figure 2, the breakdown electric field strength is increased to 500MV / m and the discharge energy density is 9.77J / cm 3 , the charge and discharge efficiency is 41.7%.

[0053] Example 3: The raw materials involved in this example include P (VDF-HFP) and BAPS.

[0054] The preparation steps are as follows:

[0055] 1. Poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS) were mixed in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. 0.19g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 0.01g of bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS) were weighed and 10ml of DMF was added to prepare a solution.

[0056] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0057] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0058] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0059] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0060] 6. Place the aluminum foil wrapped with the film into a vacuum oven and dry it at 120°C for 10 hours to obtain a P(VDF-HFP) / BAPS (5wt%) slightly cross-linked network fluorine-containing ferroelectric polymer film.

[0061] Implementation effect: The P(VDF-HFP) / BAPS (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this embodiment has a higher dielectric constant, such as Figure 6 As shown, its dielectric constant is 8.31 at 1kHz; its energy storage density and charge and discharge efficiency are shown in Figure 3 As shown in Figure 2, the breakdown electric field strength is increased to 350MV / m and the discharge energy density is 4.11J / cm 3 , the charge and discharge efficiency is 49.8%.

[0062] Example 4: The raw materials involved in this example include P (VDF-HFP) and BTMB.

[0063] The preparation steps are as follows:

[0064] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and (BTMB) in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. Weigh 0.19g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), 0.01g of (BTMB), and add 10ml of DMF to prepare a solution.

[0065] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0066] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0067] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0068] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0069] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / BTMB (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0070] Implementation effect: The P(VDF-HFP) / BTMB (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this embodiment has a higher dielectric constant, such as Figure 6 As shown, its dielectric constant is 8.85 at 1kHz; its energy storage density and charge and discharge efficiency are shown in Figure 4 As shown in Figure 2, the breakdown electric field strength is increased to 450MV / m and the discharge energy density is 7.71J / cm 3 , the charge and discharge efficiency is 41.3%.

[0071] Comparative Example 1: The raw materials involved in this comparative example include P (VDF-HFP).

[0072] The preparation steps are as follows:

[0073] 1. Weigh 0.2 g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and add 10 ml of DMF to prepare a solution.

[0074] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0075] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0076] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and a film is obtained after natural cooling to room temperature.

[0077] 5. Soak the glass slide with the film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0078] 6. Place the aluminum foil wrapped with the film into a vacuum oven and dry it at 120° C. for 10 hours to obtain a P (VDF-HFP) polymer dielectric film.

[0079] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 1 As shown, it has low energy storage density and efficiency. When the electric field strength is 400MV / m, the charge and discharge efficiency is only 37.33%, and the discharge energy density is 6.02J / cm 3 The SEM image of the brittle fracture surface of the fluorine-containing ferroelectric polymer film is shown in Figure 8 shown.

[0080] Comparative Example 2: The raw materials involved in this comparative example include P (VDF-HFP) and ODA.

[0081] The preparation steps are as follows:

[0082] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 4,4′-diaminodiphenyl ether (ODA) in a mass ratio of 99.75:0.25 to prepare a solution with a concentration of 0.25wt%. Weigh 0.1995g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), 0.0005g of 4,4′-diaminodiphenyl ether (ODA), and add 10ml of DMF to prepare a solution.

[0083] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0084] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0085] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0086] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0087] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / ODA (0.25wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0088] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) / ODA (0.25wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 1 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 500MV / m, the charge and discharge efficiency is 47.97%, and the discharge energy density is 9.1J / cm 3 .

[0089] Comparative Example 3: The raw materials involved in this comparative example include P (VDF-HFP) and ODA.

[0090] The preparation steps are as follows:

[0091] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 4,4′-diaminodiphenyl ether (ODA) in a mass ratio of 90:10 to prepare a solution with a concentration of 10wt%. Weigh 0.180g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), 0.020g of 4,4′-diaminodiphenyl ether (ODA), and add 10ml of DMF to prepare a solution.

[0092] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0093] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0094] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0095] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0096] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / ODA (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0097] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) / ODA (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 1 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 500MV / m, the charge and discharge efficiency is 43.12%, and the discharge energy density is 8.3J / cm 3 .

[0098] Comparative Example 4: The raw materials involved in this comparative example include P (VDF-HFP) and HFBAPP.

[0099] The preparation steps are as follows:

[0100] 1. Poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) were mixed in a mass ratio of 90:10 to prepare a solution with a concentration of 10wt%. 0.18g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 0.02g of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) were weighed and 10ml of DMF was added to prepare a solution.

[0101] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0102] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0103] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0104] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0105] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / HFBAPP (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0106] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) / HFBAPP (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 2 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 500MV / m, the charge and discharge efficiency is 36.57%, and the discharge energy density is 8.48J / cm 3 .

[0107] Comparative Example 5: The raw materials involved in this comparative example include P (VDF-HFP) and BAPS.

[0108] The preparation steps are as follows:

[0109] 1. Poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS) were mixed in a mass ratio of 90:10 to prepare a solution with a concentration of 10 wt%. 0.18 g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and 0.02 g of bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS) were weighed and 10 ml of DMF was added to prepare a solution.

[0110] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0111] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0112] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0113] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0114] 6. Put the aluminum foil wrapped with the film into a vacuum oven and dry it at a high temperature of 120° C. for 10 hours to obtain a P(VDF-HFP) / BAPS (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

[0115] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) / BAPS (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 3 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 350MV / m, the charge and discharge efficiency is 45.06%, and the discharge energy density is 4.3J / cm 3 .

[0116] Comparative Example 6: The raw materials involved in this comparative example include P (VDF-HFP) and BTMB.

[0117] The preparation steps are as follows:

[0118] 1. Mix poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)) and BTMB in a mass ratio of 90:10 to prepare a solution with a concentration of 10wt%. For example, weigh 0.18g of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), 0.02g of BTMB, and add 10ml of DMF to prepare a solution.

[0119] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0120] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0121] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0122] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0123] 6. Place the aluminum foil wrapped with the film into a vacuum oven and dry it at 120°C for 10 hours to obtain a P(VDF-HFP) / BTMB (10wt%) slightly cross-linked network fluorine-containing ferroelectric polymer film.

[0124] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-HFP) / BTMB (10wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 4 As shown, it has lower energy storage density and energy storage efficiency. When the electric field strength is 350MV / m, the charge and discharge efficiency is 41.69%, and the discharge energy density is 4.46J / cm 3 .

[0125] Comparative Example 7: The raw materials involved in this comparative example include P (VDF-TrFE-CFE) and ODA.

[0126] The preparation steps are as follows:

[0127] 1. P(VDF-TrFE-CFE) and ODA are mixed in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. For example, 0.19g of P(VDF-TrFE-CFE), 0.01g of ODA are weighed and 10ml of DMF is added to prepare a solution.

[0128] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0129] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0130] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0131] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0132] 6. Place the aluminum foil wrapped with the film into a vacuum oven and dry it at 120°C for 10 hours to obtain a fluorine-containing ferroelectric polymer film with a slightly cross-linked network of P(VDF-TrFE-CFE) / ODA (5wt%).

[0133] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-TrFE-CFE) / ODA (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 5 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 250MV / m, the charge and discharge efficiency is 20.44%, and the discharge energy density is 2.54J / cm 3 .

[0134] Comparative Example 8: The raw materials involved in this comparative example include P (VDF-TrFE-CFE) and HFBAPP.

[0135] The preparation steps are as follows:

[0136] 1. P(VDF-TrFE-CFE) and HFBAPP are mixed in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. For example, 0.19g of P(VDF-TrFE-CFE), 0.01g of HFBAPP are weighed and 10ml of DMF is added to prepare a solution.

[0137] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0138] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0139] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0140] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0141] 6. Place the aluminum foil wrapped with the film in a vacuum oven and dry it at 120°C for 10 hours to obtain a fluorine-containing ferroelectric polymer film with a slightly cross-linked network of P(VDF-TrFE-CFE) / HFBAPP (5wt%).

[0142] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-TrFE-CFE) / HFBAPP (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 5 As shown, it has lower energy storage density and energy storage efficiency. When the electric field strength is 350MV / m, the charge and discharge efficiency is 22.2%, and the discharge energy density is 4.43J / cm 3 .

[0143] Comparative Example 9: The raw materials involved in this comparative example include P (VDF-TrFE-CFE) and BAPS.

[0144] The preparation steps are as follows:

[0145] 1. P(VDF-TrFE-CFE) and BAPS are mixed in a mass ratio of 95:5 to prepare a solution with a concentration of 5wt%. For example, 0.19g of P(VDF-TrFE-CFE), 0.01g of BAPS are weighed and 10ml of DMF is added to prepare a solution.

[0146] 2. The above solution was dissolved and dispersed at 60°C with magnetic stirring for 10 hours to allow the solute to be fully and evenly dissolved in the solvent.

[0147] 3. Clean the glass slide to avoid dust contamination, then put the glass slide in a 70℃ oven for preheating for half an hour, then use a rubber-tipped dropper to absorb 5 ml of the above mixed solution and add it to the glass slide, let the solution flow naturally on the glass slide, and bake it in a 70℃ oven for 10 hours to evaporate the solvent.

[0148] 4. After the solvent has evaporated, the glass sheet is placed in a vacuum oven and the temperature is adjusted to perform a multi-stage high-temperature reaction. The temperature and time of each stage are: 120°C for ten hours, 240°C for one hour, and then naturally cooled to room temperature to obtain a cross-linked film.

[0149] 5. Soak the glass slide with the lightly cross-linked film in deionized water. After a period of time, the film will fall off the glass slide by itself. Wrap the fallen film with aluminum foil.

[0150] 6. Place the aluminum foil wrapped with the film into a vacuum oven and dry it at 120°C for 10 hours to obtain a fluorine-containing ferroelectric polymer film with a slightly cross-linked network of P(VDF-TrFE-CFE) / BAPS (5wt%).

[0151] Comparative effect: The energy storage density and charge-discharge efficiency of the P(VDF-TrFE-CFE) / BAPS (5wt%) diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film prepared in this comparative example are as follows: Figure 5 As shown in Figure 2, it has a lower energy storage density and energy storage efficiency. When the electric field strength is 300MV / m, the charge and discharge efficiency is 19.1%, and the discharge energy density is 3.68J / cm 3 .

[0152] In summary, the film prepared by the present invention meets the application requirements of improving the dielectric constant under high field, reducing the dielectric loss, reducing the leakage current and improving the breakdown field strength. The addition of diamine monomer improves the crystallinity and β-phase content of the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer as the matrix.

[0153] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0154] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer, characterized in that: Its components include semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and diamine crosslinking agent; the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer is polyvinylidene fluoride and its copolymer derivatives with ferroelectricity; the diamine crosslinking agent is a short-chain diamine with a rigid structure; the mass fraction of the diamine crosslinking agent compared to the whole is 0.25%-10%.

2. The diamine monomer cross-linked modified fluorine-containing ferroelectric polymer according to claim 1, characterized in that: Semi-crystalline thermoplastic fluorine-containing ferroelectric polymers include polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trifluoroethylene), and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene).

3. The diamine monomer cross-linked modified fluorine-containing ferroelectric polymer according to claim 1, characterized in that the diamine monomer Amine crosslinking agents include diaminodiphenylmethane, diaminodiphenyl sulfone, 4,4′-diaminodiphenyl ether, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, and 2,2′-bis(trifluoromethyl)diaminobiphenyl.

4. The diamine monomer cross-linked modified fluorine-containing ferroelectric polymer according to claim 1, characterized in that: The mass fraction of the diamine crosslinking agent is 0.5%-5% compared to the total mass fraction.

5. The method for preparing the diamine monomer cross-linked modified fluorine-containing ferroelectric polymer according to any one of claims 1 to 4, characterized in that: The following steps are involved: A semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and a diamine monomer are subjected to a heat-induced high-temperature cross-linking reaction to prepare a slightly cross-linked fluorine-containing ferroelectric polymer film; first, the semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and the diamine monomer are blended and prepared into an uncross-linked film by a solution casting method; Then, the film is treated at high temperature in a vacuum environment to induce a cross-linking reaction between the diamine monomer and the fluorine-containing ferroelectric polymer to form a fluorine-containing ferroelectric polymer film with a slightly cross-linked network.

6. The method for preparing a fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer according to claim 5, characterized in that: It includes the following sub-steps: S1. The semi-crystalline thermoplastic fluorine-containing ferroelectric polymer and the diamine crosslinking agent are dissolved in an organic solvent, heated to dissolve, and a slurry of the composition is obtained, wherein the solid content of the slurry is 0.1wt%-20wt%; S2. The slurry is formed into a film by a solution casting method; specifically, the slurry is evenly coated on a glass substrate and baked at 60-90°C to evaporate the solvent as much as possible to obtain an uncrosslinked film; S3. After the solvent is evaporated, the glass substrate is subjected to a cross-linking reaction at multiple temperatures between 100°C and 250°C to obtain a cross-linked film; S4. Put the glass substrate with the cross-linked film into deionized water to peel off the film, and dry the peeled film at high temperature to obtain a diamine monomer cross-linked modified fluorine-containing ferroelectric polymer film.

7. The method for preparing a fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer according to claim 6, characterized in that: In step S1, the solid content of the slurry is 1wt%-2wt%.

8. The method for preparing a fluorine-containing ferroelectric polymer cross-linked and modified by a diamine monomer according to claim 6, characterized in that: In step S3, the cross-linking process is 120°C×10h+240°C×1h.

9. A device, characterized in that The fluorine-containing ferroelectric polymer cross-linked and modified by the diamine monomer as described in any one of claims 1 to 4 is used as a film capacitor.

Citation Information

Patent Citations

  • Resilient ferroelectric and preparation method and application thereof

    CN116574344A

  • Polymer and polymer actuator comprising the same

    US20100201227A1

Cited By

  • Grafted ferroelectric polymer film with high piezoelectric coefficient and preparation method thereof

    CN121159905A

  • Ferroelectric polymer and method for preparing ferroelectric polymer through crosslinking modification

    CN121270771A